Combined Effects of Breathing Exercise and Core Strength Training on Fatigue, Abdominal Strength, and Cardiovascular Fitness among Subjects with Mechanical Nonspecific Lumbago Using Tele-physiotherapy: A Randomized Clinical Trial - Sawant, Komal Umesh; Rai, Richa Hirendra; Kalra, Sheetal; Sharma, Abhishek; Chahal, Aksh; Sharma, Nidhi (Journal of Datta Meghe Institute of Medical Sciences University, 2024)
Abstract Background: Lumbago is derived from the word "lumbar region." This pain in the lower back/lumbar region is addressed low back pain (LBP). It is considered a major health issue causing disability, and associated with increased fatigue level, decreased abdominal strength, and poor cardiovascular fitness in the affected population. Objectives of the Study: Isolate and configure combined effect of breathing exercise and core strengthening training on fatigue, abdominal strength, and cardiovascular fitness in mechanical nonspecific lumbago subjects using tele-physiotherapy. Methods: A two-group online randomized control trial was conducted involving 60 participants. The duration of the study stretched for 4 weeks. Subjects recruited in accordance with the inclusion and exclusion criteria were split into two groups, i.e., experimental and control groups. The experimental group performed core strength training and breathing exercises, whereas the control group performed only core strength training. Before exercise and at the end of each week fatigue, abdominal strength, and VO2max of the subjects were measured and evaluated. Results: Results from the present study concluded significant improvement within each group fatigue, abdominal strength (P < 0.05). However, no between groups difference was observed for VO2max (P > 0.05). Pain intensity perceived by the patients was improved in the group subjected to combined intervention involving core strengthening and breathing exercises as compared to the control group. Conclusion: The study proposed a significant effect of breathing exercise along with core strength training on parameters of fatigue, abdominal strength, and cardiovascular fitness in subjects with lumbago.